The value of routine ultrasound at discharge to identify patients at risk of developing symptomatic lymphoceles after kidney transplantation: A case-cohort study - Joosten, Maja; Poyck, Paul P; d’Ancona, Frank C; Meijden, Wilbert A van der (Journal of Clinical Nephrology, 2019)
Introduction: Ultrasound examination is frequently used to evaluate the graft after renal transplantation and to detect possible lymphoceles. The first ultrasound scan in our hospital is normally performed on the day of discharge. We questioned whether perirenal fluid collections detected by ultrasound examination at discharge are predictive for future symptomatic lymphoceles. Methods: All ultrasound reports of all renal transplant recipients treated in our hospital between January 2010 and December 2017 were collected and screened for abnormalities such as fluid collections. Patients that developed a symptomatic lymphocele were compared with a control group from the same cohort. Sensitivity and specificity of ultrasound examination to detect symptomatic lymphoceles were calculated for the primary and consecutive ultrasounds tests. Results: There were no significant differences at baseline characteristics between the Symptomatic lymphocele group and control group, with the exception of mean age at kidney transplantation (47 ± 17 years in the control group vs. 56 ± 13 years in the symptomatic lymphocele group, p=0.02). The ultrasound examination at discharge had a sensitivity of 31% and specificity of 87% to detect future symptomatic lymphoceles. The positive predictive value was only 10%. The second ultrasound test had the best test variables to detect symptomatic lymphoceles with a sensitivity of 93% and a specificity of 87% and a predictive value of 28%. Conclusion: Routinely use of ultrasound testing on the day of discharge does detect perirenal fluid collections, but is not predictive for development of symptomatic lymphoceles in the future.